2018
DOI: 10.1113/jp275288
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of small ubiquitin‐like modifiers during human placental development and in response to oxidative and inflammatory stress

Abstract: Key points The post‐translational modification of target proteins by SUMOylation occurs in response to stressful stimuli in a variety of organ systems.Small ubiquitin‐like modifier (SUMO) isoforms 1–4 have recently been identified in the human placenta, and are upregulated in the major obstetrical complication of pre‐eclampsia.This is the first study to characterize the spatiotemporal distribution of SUMO isoforms and their targets during placental development across gestation and in response to stress induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 56 publications
(114 reference statements)
4
17
0
1
Order By: Relevance
“…19 Our findings support the critical functions of SUMO2 and SUMO3 in placentation. Placental defects caused by hyper-SUMOylation in the SENP2 knockouts can be alleviated by the reduction of SUMO modifiers.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…19 Our findings support the critical functions of SUMO2 and SUMO3 in placentation. Placental defects caused by hyper-SUMOylation in the SENP2 knockouts can be alleviated by the reduction of SUMO modifiers.…”
Section: Discussionsupporting
confidence: 78%
“…SUMO2/3 has not only a much wider expression pattern in the trophoblast lineages and cell types, but also distinct stress responses compared to the SUMO1, implying a functional difference between SUMO1 and SUMO2/3 during placental development. 19 Our findings support the critical functions of SUMO2 and SUMO3 in placentation. Reducing the level of SUMO2 or SUMO3 successfully alleviates the developmental defects of the trophoblast layers, suggesting their involvement in hyper-SUMOylation caused by the loss of SENP2.…”
Section: Discussionsupporting
confidence: 78%
“…Baczyk et al . () also demonstrated that under oxidative stress conditions, which mimic the placenta compromised by PE, hyperSUMOylation of SUMO‐1 and SUMO‐4 was induced, as well as translocation of SUMO‐2/3 to the nuclear region (Baczyk et al . ).…”
mentioning
confidence: 98%
“…() also demonstrated that under oxidative stress conditions, which mimic the placenta compromised by PE, hyperSUMOylation of SUMO‐1 and SUMO‐4 was induced, as well as translocation of SUMO‐2/3 to the nuclear region (Baczyk et al . ). In placentas compromised by PE, as well as normal placental explants exposed to oxidative stress, expression of SUMO‐1 and SUMO‐4 proteins was increased in the cytoplasm.…”
mentioning
confidence: 99%
See 1 more Smart Citation